Effect of quantum confinement on lifetime of anharmonic decay of optical phonons in semiconductor nanostructures. (7th August 2018) - Datta, D; Krishnababu, K; Stroscio, M A; Dutta, M
Abstract: The anharmonic decay of phonons underlies many important effects in semiconductors, e.g. hotspot formation, phonon bottleneck and thermal resistivity. In this article, we evaluate the effect of quantum confinement on the anharmonic decay transition probability in a cubic isotropic material. This article focuses on the anharmonic decay of longitudinal optical phonons, generated from hot electrons, are directly related to formation of hotspots in the active region of semiconductor devices. The confinement effect has been realized in double interface heterostructure quantum well (DHSQW) (e.g. AlAs/GaAs/AlAs) and free-standing quantum well (FSQW) (e.g. GaAs) structures as the confined phonon modes have different properties inside the structures. The longitudinal–optical phonon decay rate is reduced for the case of a DHSQW compared to bulk material and for a FSQW the decay rate has a strong dependence on wavevector value of the three phonons involved.